Eksplorasi Pengaruh Kreativitas dan Inovasi Terhadap Keberhasilan Wirausaha Muda : Studi Kasus Wisata Tepi Laut - Nuraisyah Nuraisyah; Gita Farista; Reza Apriansyah; Fira Ria Idul Fitri; Rahmadini Rahmadini (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the influence of creativity and innovation on entrepreneurial success. This type of research uses descriptive qualitative research methods. Research subject, seaside tourism entrepreneur owner. The research object is entrepreneurial exploration, including planning, implementation and evaluation processes. The method used to collect data is observation, interviews and documentation.